Inhibition of N-cadherin retards smooth muscle cell migration and intimal thickening via induction of apoptosis - Lyon, Cressida A. (Elsevier, 2010)
OBJECTIVES: Inhibition of vascular smooth muscle cell (VSMC) migration is a potential strategy for reducing intimal thickening during in-stent restenosis and vein graft failure. In this study, we examined the effect of disrupting the function of the VSMC adhesion molecule, N-cadherin, using antagonists, neutralizing antibodies, and a dominant negative, on VSMC migration and intimal thickening. Migration was assessed by the scratch-wound assay of human saphenous vein VSMCs and in a human saphenous vein ex vivo organ culture model of intimal thickening. RESULTS: Inhibition of cadherin function using a pan-cadherin antagonist, significantly reduced migration by 53% ± 8% compared with the control peptide (n = 3; P < .05). Furthermore, inhibition of N-cadherin function with an N-cadherin antagonist, neutralizing antibodies, and adenoviral expression of dominant negative N-cadherin (RAd dn-N-cadherin), significantly reduced migration by 31% ± 2%, 23% ± 1% and 32% ± 7% compared with controls, respectively (n = 3; P < .05). Inhibition of cadherin function significantly increased apoptosis by between 1.5- and 3.3-fold at the wound edge. In an ex vivo model of intimal thickening, inhibition of N-cadherin function by infection of human saphenous vein segments with RAd dn-N-cadherin significantly reduced VSMC migration by 55% and increased VSMC apoptosis by 2.7-fold. As a result, intimal thickening was significantly suppressed by 54% ± 14%. Importantly, there was no detrimental effect of dn-N-cadherin on endothelial coverage; in fact, it was significantly increased, as was survival of cultured human saphenous vein endothelial cells. CONCLUSIONS: Under the condition of this study, cell-cell adhesion mediated by N-cadherin regulates VSMC migration via modulation of viability. Interestingly, inhibition of N-cadherin function significantly retards intimal thickening via inhibition of VSMC migration and promotion of endothelial cell survival. We suggest that disruption of N-cadherin-mediated cell-cell contacts is a potential strategy for reducing VSMC migration and intimal thickening.